Risk Factors for Proximal Neck Complications After Endovascular Aneurysm Repair Using the Endurant Stentgraft. Issue 2 (February 2015) - Bastos Goncalves, F.; Hoeks, S.E.; Teijink, J.A.; Moll, F.L.; Castro, J.A.; Stolker, R.J.; Forbes, T.L.; Verhagen, H.J.M.
Abstract : Objective: To assess the incidence and risk factors for proximal aneurysm neck related complications with a late generation device for endovascular abdominal aneurysm repair (EVAR). Methods: Data were retrieved from a prospective registry (Endurant Stent Graft Natural Selection Global Postmarket Registry) involving 79 institutions worldwide. The risk factors tested were age, gender, surgical risk profile, proximal neck length (<10 mm), diameter (>30 mm), supra- and infrarenal angulation (>60° and 75°), mural thrombus/calcification (>50%) and taper (>10%), and AAA diameter (>65 mm). Two neck related composite endpoints were used, for intra-operative (type-1a endoleak, conversion, deployment/retrieval complication or unintentional renal coverage) and post-operative (type-1a endoleak or migration) adverse events. Independent risk factors were identified using multivariable backwards modeling. Results: The study included 1263 patients (mean age 73, 10.3% female) from March 2009 to May 2011. Twenty three (1.8%) intra-operative adverse events occurred. Neck length <10 mm (OR 4.9, 95% CI 1.1–22.6) and neck thrombus/calcification >50% (OR 4.8, 95% CI 1.7–13.5) were risk factors for intra-operative events. The planned 1 year follow up visit was reached for the entire cohort, and the 2 year visit for 431 patients. During this time, 99 (7.8%) events occurred. Female gender (HR 1.9, 95% CI 1.1–3.2), aneurysm diameter >65 mm (HR 2.8, 95% CI 1.9–4.2), and neck length <10 mm (HR 2.8, 95% CI 1.1–6.9) were significant post-operative risk factors. Neck angulation, neck taper, large diameter neck, and presence of thrombus/calcification were not predictors of adverse outcome in this study. Conclusion: These results support the adequacy of this device in the face of adverse neck anatomy, and confirm neck length as the most relevant anatomical limitation for EVAR. Additionally, the study confirms the decline in early to mid-term intervention rates with a newer generation device in a large patient sample. Lastly, it suggests that neck related risk factors affect outcome and impact on prognosis in varying degrees.